Changes of Soil Microbial Characteristics and Nutrient Content in Sandy Soil Under Drip Irrigation System - Gaballah, Maybelle; Ragab, Samar; El-Gindy, Abdel-Ghany; Arafa, Yasser (Indonesian Journal of Agricultural Research, 2024)
A field experiment was conducted to investigate the changes in soil bacteria when using the bio fertilizers such as; azotobacter, bacillus circullans and bacillus megaterium in sandy soils across varied numbers of cultivated years using drip irrigation. Drip irrigation had a significant effect on bacterial levels. The biological qualities of the soil improved significantly as the number of years planted under drip irrigation rose. After two years of cultivation, the bacterial levels increased 102 times more than on uncultivated ground. The vertical direction, the number of bacterial colonies reduced as soil depth increased. The Bio-fertilizer treatment improved soil fertility more than any other therapy. The average total N, total P, and total K in 0-45 cm soil layers rose to 29.17, 26.67, and 36.7%, respectively. The soil environment was considerably improved, with significant positive relationships between bacterial, phosphate, and urea activity, as well as significant negative correlations with Ece and pH. We anticipate that soil microbial properties in drip-irrigated sandy soils will improve after 6-7 years of cultivation.